An Empirical Study of IPO Underpricing in China: The IPO Systems Evolution and Determinants with Quantile Regression - Xu, Qianru (2018)
This paper interprets and analyses the phenomenon of IPO underpricing in China with considering four transitions in Chinese IPO regulation systems. Firstly, one-way ANOVA is applied using 3,343 Chinese IPOs from 1993 to 2018 to test the IPO system transitions’ influence on IPO underpricing level. The empirical result indicates that the transitions in IPO system have profound impacts on the improvement of IPO underpricing phenomenon in Chinese primary market. Secondly, OLS and quantile regressions are conducted to find out key factors can influence the magnitude of IPO underpricing using 2,142 IPOs between 2006 and 2018. According to the comprehensive regressions results, 5 variables including issuing price, issuing size, time interval, over-subscription ratio, and agency cost ratio are significant determinants of IPO underpricing. However, both initial turnover rate and underwriter reputation do not show significant effect on the magnitude of underpricing. Most of these findings are consistent with information asymmetry theory and Chinese capital market characteristics.